Analysis of Regional Financial Capabilities and Independence and Their Effect on Economic Growth in Bali Province in 2019–2021 - Diputra, Gde Indra Surya (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2024)
While financial independence and regional economic growth have been recognized as key factors in public sector success, there is limited understanding of the specific dynamics in Bali Province, especially during the pandemic period of 2019-2021. This knowledge gap hinders an accurate evaluation of regional financial capability and independence, as well as their impact on Bali's economic growth. Thus, the purpose of this study was to analyze and describe the impact of regional financial capacity and independence on economic growth in Bali during 2019-2021. A quantitative descriptive research design was employed, using multiple linear regression analysis at a 95% confidence level (p<0.05). The results showed that both regional financial capacity and independence had a significant effect on economic growth in Bali. The analysis indicates that the regional financial independence ratio during 2019-2021 was low, showing an instructive relationship pattern. Meanwhile, the regional financial capacity ratio, though relatively limited, showed a positive relationship pattern. Additionally, fiscal decentralization and economic growth were found to negatively affect Bali’s poverty rate from 2003 to 2011. Overall, regional financial capacity and independence were shown to have a significant impact on the region’s economic growth. Further research is needed to explore the predisposing factors that affect economic growth, both external and internal